Dietary preferences and analysis of the "plant-based food basket" among Ukrainian preteens and teenagers - Filiptsova, Olga; Naboka, Olga; Bobro, Svitlana; Bashura, Olexander; Myrhorod, Vira; Osypenko, Yuliia; Petrovska, Liudmyla (ScienceRise: Biological Science, 2023)
The aim. The aim of the study was to analyze aspects related to a healthy diet and lifestyle, more specifically to the consumption of plant-based food among Ukrainian preteens and teenagers aged 10 to 17 years. Materials and methods. 231 individuals aged 10 to 17 participated in the study, 85 of them were boys, 146 were girls, all of them were residents of Kharkiv city at the time of participation in the study. The respondents were presented with a questionnaire regarding their attitude to a healthy lifestyle, in particular, rational nutrition. The χ2 test was used to analyze the qualitative data. Results and discussion. In the work, it was found that more than half of the respondents led only a partially healthy lifestyle, 60.3 % and 54.1 % among girls and boys, respectively. Only 11.6 % and 18.8 % of girls and boys followed the diet, although the majority of preteens and teenagers did not skip breakfast (80.8 % of girls and 89.4 % of boys). Unfortunately, the vast majority of subjects (58.9 % of girls and 56.5 % of boys) sometimes indulged in "harmful food". Also, the majority of preteens and teenagers consumed food between principal meals (83.6 % of girls and 72.9 % of boys), which, taking into account current ideas, should be considered an alarming trend. The main motivation for choosing food among preteens and teenagers was their own food tastes and family traditions, while food advertising was taken into account by just over 1 % of preteens and teenagers. Self-assessment of the health state shows that only 2/3 to ¾ of preteens and teenagers had no complaints about their health. No sex differences were observed for all the indicated characteristics. The most popular vegetable product among Ukrainian preteens and teenagers was potato, it was consumed by more than ¾ of preteens and teenagers, its popularity grew with age, which can be considered a negative trend (fast food). The least popular plant-based product among preteens and teenagers was seeds, consumed by only 19.9 % of girls and 8.2 % of boys. It was the only plant-based product, for which a statistically significant difference in consumption was found (2.4 times more common among girls than among boys). With age, the frequency of coffee consumption as an "adult drink" increased among preteens and teenagers, while a "leap" in the prevalence of its consumption can be seen when passing from 14-15 years to 16-17 years. Therefore, most of the results obtained should be considered as concerning ones. Conclusions. The consumption of plant-based food among Ukrainian preteens and teenagers is almost not associated with sex, while the consumption of some types of plant-based food is more closely related to the age of preteens and teenagers, which may indicate the continuation of the process of forming food habits in this ontogenesis period. The practical value of the work lies in potential corrective recommendations from doctors, valeologists, nutritionists, psychologists and other related specialists